2021
DOI: 10.3349/ymj.2021.62.8.708
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Seven-Day Potassium-Competitive Acid Blocker-Based First-LineHelicobacter PyloriEradication Therapy Administered with Bismuth

Abstract: Purpose To determine the efficacy of a potassium-competitive acid blocker (P-CAB)-based first-line eradication therapy with bismuth compared with that of proton pump inhibitor-based first-line therapy with bismuth. Materials and Methods Eradication-naive H. pylori -infected patients were consecutively enrolled from January to November 2020. Before approval of the P-CAB-based eradication therapy, twice daily administration of a regimen containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…To date, two studies have compared the effects of tegoprazan and PPIs in H. pylori eradication. 30,31 One retrospective study by Kim et al, 30 published in 2021, assessed the comparative efficacy of bismuth-containing quadruple regimens consisting of 50 mg tegoprazan, 30 mg lansoprazole, 1,000 mg amoxicillin, 500 mg clarithromycin, and 300 mg bismuth potassium citrate administered twice daily for 7 days. Consistent with our findings, this study did not demonstrate superior efficacy of tegoprazan-based therapy compared with PPI-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, two studies have compared the effects of tegoprazan and PPIs in H. pylori eradication. 30,31 One retrospective study by Kim et al, 30 published in 2021, assessed the comparative efficacy of bismuth-containing quadruple regimens consisting of 50 mg tegoprazan, 30 mg lansoprazole, 1,000 mg amoxicillin, 500 mg clarithromycin, and 300 mg bismuth potassium citrate administered twice daily for 7 days. Consistent with our findings, this study did not demonstrate superior efficacy of tegoprazan-based therapy compared with PPI-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on tegoprazan-based therapy for 7 days in Korea showed an unsatisfactory eradication rate (79% and 88% in ITT and PP analyses, respectively) even though the regimen contained bismuth to increase the eradication rate. 12 Therefore, 14-day treatment should be considered when triple therapy is selected empirically in regions with high clarithromycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Even though P‐CAB has a fast onset of action and strong acid‐inhibitory potency, P‐CAB‐based triple therapy for 7 days may be insufficient in regions with high clarithromycin resistance. A recent study on tegoprazan‐based therapy for 7 days in Korea showed an unsatisfactory eradication rate (79% and 88% in ITT and PP analyses, respectively) even though the regimen contained bismuth to increase the eradication rate 12 . Therefore, 14‐day treatment should be considered when triple therapy is selected empirically in regions with high clarithromycin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tegoprazan 50 mg combined with amoxicillin and clarithromycin did not achieve an acceptable eradication rate. [ 36 ] Authors explained that tegoprazan 50 mg (twice the dose used for gastroesophageal reflux disease) appears insufficient in suppressing the gastric acid and in achieving an acceptable eradication rate. In triple therapy with vonoprazan, the 20 mg dose is 4 times the dose used for gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%